Slope Failure Due to Effect of Damrey Typhoon in Penang Island - F. Ahmad; A.S. Yahaya; M Azmi; N. Muztaza (Lowland Technology International, 2020)
The monsoon season in month of November till December in2017 has left Penang Island in devastated conditions where, hillslope landslide, erosion and flood took place around Penang.This was a monsoon season, however these occurrences werenot normal and Penang has accounted many slope failure,building construction collapse and flash floods. A series of failureoccurred at the surrounding slope at USM has occurred over thepast 10 years and therefore remedial work were carry out toimprove the slope on site. During the seasonal rainfalls, the slopewas heavily eroded and all the trees and grouted slope whichwas in placed before, fail to sustain from the water movement.Then a series of Soil Resistivity test on site was then explored toforesee the major problems and to counter the stability. By doingthis investigation, the purpose is to understand, analyse andrectify the situation of slope failure. From this study, we haveconducted the soil mapping of the ground to further understandthe soil condition so that all the